Implementation of Servant Leadership and Its Impact on Service Quality - Harnida W. Adda; Pricylia Chintya Dewi Buntuang; Armawati Sondeng (Budapest International Research and Critics University, 2021)
This study aims to examine the impact of the implementation of servant leadership on service quality at the Morowali Population and Civil Registration Agency. It used a quantitative approach and descriptive statistics analysis. The sample was all employees and service users (communities) at Morowali Population and Civil Registration Agency. The data were collected through observations, questionnaires, and documentation. The results show that the servant leadership has not been properly implemented causing slow, less assured, and less reponsive services at Morowali Population and Civil Registration Agency.